Middle to Late Holocene palaeoenvironmental evolution of the western Great Rann of Kachchh, India: Insights from ichnology, geochemistry, and sedimentology. Issue 9 (1st July 2022) - Padia, Darshit; Desai, Bhawanisingh; Chauhan, Suruchi; Prizomwala, Siddharth; Chauhan, Gaurav; Thakkar, M. G.
Abstract : To understand the palaeoenvironmental changes during the Middle to Late Holocene period, we have carried out multiproxy analysis integrating ichnology, geochemistry, and sedimentology in the Great Rann of Kachchh (GRK). The exposed cliff sections of Rann sediments and overlying Bet sediments are explored and analysed for the characteristics of the sedimentary sequences and ichnological assemblages. Seven recurring ichnotaxa are documented, which comprise of Arenicolites, Paleophycus, Planolites, Psilonichnus, Skolithos, Teichichnus, and Thalassinoides . The ichnological and sedimentological findings were supported by obtained geochemical results, which were then compared with the existing chronological data. The trace fossils associated with the bottom of the Bet Zone and the top surface of the Great Rann sediment units (Middle Holocene) suggest the shallow marine depositional environment. Further, the monospecific occurrence of Teichichnus in the middle units (Middle to Late Holocene period) of the Bet Zone sediments suggests the brackish water environmental conditions associated with the high discharge of fluvial system leading to lowering of salinity. The topmost unit of the Bet Zone sediments shows the disappearance of trace fossils suggesting a terrestrial depositional condition. The present work suggests that the area of the western GRK has witnessed a gradual shifting of shallow marine to the fluvial environment during the Middle to Late Holocene period. Abstract : Middle to Late Holocene palaeoenvironment reconstruction of Great Rann of Kachchh integrates ichnology, sedimentology, and geochemistry for deducing marine to brackish environment transition in the Rann sediments.